2009
DOI: 10.1111/j.1537-2995.2009.02320.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the persistence and characteristics of indeterminate reactivity against hepatitis C virus in blood donors

Abstract: Indeterminate HCV RIBA reactivity in blood donors persists over years. Increased prevalence during autumn and winter and association to detection of adenovirus antibody indicate that viral infection and cross-reactivity are etiologic factors in indeterminate HCV RIBA reactivity. Further prospective studies are needed to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…As indeterminate IB results may represent past exposure to HCV , we suggest the anti‐HCV indeterminate group in our study probably represents two populations ‐ those with non‐specific reactivity and those with past exposure to HCV and subsequent partial seroreversion. This assumption is consistent with the observed difference between the PRISM HCV ChLIA s/co ratio distribution of the indeterminate group which was significantly higher than the BFR group but significantly less than the anti‐HCV‐positive group.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…As indeterminate IB results may represent past exposure to HCV , we suggest the anti‐HCV indeterminate group in our study probably represents two populations ‐ those with non‐specific reactivity and those with past exposure to HCV and subsequent partial seroreversion. This assumption is consistent with the observed difference between the PRISM HCV ChLIA s/co ratio distribution of the indeterminate group which was significantly higher than the BFR group but significantly less than the anti‐HCV‐positive group.…”
Section: Discussionmentioning
confidence: 72%
“…However, anti‐HCV IB assays can generate indeterminate results, defined by the manufacturer as band reactivity that is insufficient to meet the criteria for a positive result. Interpreting the significance of IB indeterminate results can be difficult as HCV RNA is usually not detectable and such results may represent either past exposure to HCV or non‐specific reactivity . In a previous study of Australian blood donors with indeterminate results on the RIBA 3·0 HCV strip IB assay (Chiron Corp., Emeryville, CA, USA), a number of indicators of past exposure to HCV were identified which included the sample to cut‐off (s/co) ratio of the screening IA, IB band reactivity, risk factors for HCV infection and donation history .…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent longer term study of Australian donors with FP anti‐HTLV IA results indicated that while approximately 53% of FP results were transient (Table ), they can take several months to several years to resolve . This is also consistent with studies that have reported indeterminate anti‐HTLV and anti‐HCV IB results, even when they are considered to represent FP results, can persist for several years . Based on the results of this longer term study, the outcome of several different donor management strategies was modelled (Table ).…”
Section: False Positive Results: Unintended Consequencesmentioning
confidence: 99%
“…It is known that there are presumed false‐positive HCV donors (anti‐HCV positive, HCV NAT negative). With further complex methods evaluating for immunological response to HCV (not ready for routine screening testing) [16–18], it is known that some of these donors are truly negative, some of those negative because of seasonal viral infections [19] and some of the donors being positive having recovered from the infection. However, it is not believed that these positive donations are capable of transmitting HCV.…”
Section: Hepatitis Cmentioning
confidence: 99%